2009
DOI: 10.3168/jds.2008-1724
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of chronic gastritis by fermented milks made with exopolysaccharide-producing Streptococcus thermophilus strains

Abstract: Acetyl-salicylic acid (ASA) is a nonsteroidal antiinflammatory/analgesic drug, which may cause gastritis or stomach ulcers if intensively employed. Exopolysaccharide (EPS)-producing lactic acid bacteria have been claimed to induce immunostimulatory/antiulcer effects in the host. This study investigated the potential preventive effect of fermented milks (FM) with EPS-producing Streptococcus thermophilus strains (CRL 1190 and CRL 804) on an in vivo model of chronic gastritis. Fermented milks (2 EPS(+) and 1 EPS(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(41 citation statements)
references
References 43 publications
2
35
0
4
Order By: Relevance
“…Purified EPS from S. thermophilus CRL 1190 was found to be effective for preventing chronic gastritis [63]. The authors justified that the EPS-protein interaction might be responsible for the observed gastroprotective effect; such interactions may be affected by industrial manufacturing conditions.…”
Section: Antigastritis Antiulcer and Cholesterol Lowering Effectsmentioning
confidence: 95%
See 1 more Smart Citation
“…Purified EPS from S. thermophilus CRL 1190 was found to be effective for preventing chronic gastritis [63]. The authors justified that the EPS-protein interaction might be responsible for the observed gastroprotective effect; such interactions may be affected by industrial manufacturing conditions.…”
Section: Antigastritis Antiulcer and Cholesterol Lowering Effectsmentioning
confidence: 95%
“…It is not likely that EPS serves as a food reserve for the bacteria producing them, because most slimeforming bacteria are not capable of metabolizing the EPS they produce [61]. Apart from protection, few studies on EPS suggested that EPS produced by specific LAB could exert health beneficial effects through immunomodulation or by other means [36,62,63], some of these observations are discussed below.…”
Section: Physiological Functions Of Epsmentioning
confidence: 99%
“…9,10) EPSs have been shown to benefit human health by their immunomodulation, anti-gastritis, anti-ulcer, and anti-virus activities. [11][12][13] We have shown that P. pentosaceus LP28 has the strain-specific EPS biosynthetic gene cluster, 14) and intake of the strain is effective to improve the high fat diet-induced obesity and fatty liver of the mice. 6) Furthermore, the strain is also useful to reduce body fat and body weight in human clinical study.…”
mentioning
confidence: 99%
“…(1994) reported anti-ulcer effects of the cell wall polysaccharide of bifidobacteria, lactobacilli and streptococci strains, which were attributed to the high rhamnose content of the polymers (> 60%). Rodríguez et al (2009Rodríguez et al ( , 2010 reported the first evidences on the beneficial effects of both the EPS-producing LAB strains and the biopolymer on gastritis experimental animal models using acetyl salicylic acid ( The strains CRL 1190 and CRL 87 also produced capsular polysaccharide in addition to the slime EPS in milk and was able to form ropy milk cultures similar to CRL 638, while the strain CRL 804 was negative for both the capsular and ropy phenotypes (Mozzi et. al., 2006).…”
Section: Wwwintechopencommentioning
confidence: 99%